Pengaruh Penambahan Rumput Laut (Eucheuma cottonii) pada Pembuatan Bakso Puyuh terhadap Sifat Fisik dan Akseptabilitas - Fatmah Nur Anggraini; Wendry Setiyadi Putranto; Lilis Suryaningsih (Jurnal Teknologi Hasil Peternakan, 2020)
Seaweed is a source of hydrocolloid carrageenan can absorb water to produce a compact texture of meatballs. Quail meat contains of high protein but low fat which is recommended as a low-fat food. The objective of research were to find out the effect and the level of seaweed (Eucheuma cottonii) on physical properties (WHC, cooking loss and tenderness) and acceptability (color, taste, smell, suppleness and total acceptance) of the most preferable quail meatball. The experiment was conducted with Compeletely Randomized Design (CRD) with four treatments: 0% (P1), 5% (P2), 10% (P3) and 15% (P4) and five replications.Analysis of variance use to determine of effect seaweed addition on physical properties of quail meatball and the Duncan’s Multiple Range Test, Kruskal Wallis test was used to determine acceptability quail meatball, and difference of various between the treatment was used Man Whitney test. Result indicated that 10% seaweed porridge produces the best physical properties WHC 43.54%, cooking loss 9.77%, tenderness 108.80 mm/g/10 seconds and acceptability with a numerical scale on total value is 2 (somewhat preferred).